Integrative Morphological, Physiological, Proteomics Analyses of Jujube Fruit Development Provide Insights Into Fruit Quality Domestication From Wild Jujube to Cultivated Jujube - Huang, Jian; Chen, Xin; He, Aobing; Ma, Zhibo; Gong, Tianqi; Xu, Kenong; Chen, Ruihong (Frontiers in Plant Science, 2021)
Jujube (Ziziphus jujuba) was domesticated from wild jujube (Z. jujuba var. spinosa). Here, integrative physiological, metabolomic, and comparative proteomic analyses were performed to investigate the fruit expansion and fruit taste components in a jujube cultivar ‘Junzao’ and a wild jujube ‘Qingjiansuanzao’ with contrasting fruit size and taste. We revealed that the duration of cell division and expansion largely determined the final fruit size, while the intercellular space in mesocarp dictated the ratio of mesocarp volume in mature fruits. The high levels of endogenous Gibberline3 and zeatin in the growing fruit of ‘Junzao’ were associated with their increased fruit expansion. Compared to ‘Junzao’, wild jujube accumulated lower sugars and higher organic acids. Furthermore, several protein co-expression modules and important member proteins correlated with fruit expansion, sugar synthesis, and ascorbic acid metabolism were identified. Among them, GA20OX involved in GA biosynthesis was identified as a key protein regulating fruit expansion, whereas SPS and NINV were considered a key enzyme promoting sugar accumulation and a major factor regulating the ratio of sucrose to hexose in jujube fruit, respectively. Moreover, the increase of NAD-MDH activity and protein abundance were associated with the malic acid accumulation, and the high accumulation of ascorbic acid in wild jujube was correlated with the elevated abundance of GalDH, ZjAPXs and MDHAR1, which are involved in the ascorbic acid biosynthesis and recycling pathways. Overall, these results deepened the understanding of mechanisms regulating fruit expansion and sugar/acids metabolisms in jujube fruit.